Inovação e Pesquisa Responsável e engajamento público da ciência: o caso das Incubadoras Tecnológicas de Cooperativas Populares de universidades públicas brasileiras - Arruda, Adriana Gonçalves (2021)
The main objective of this thesis was to investigate the presence of the public engagement of science in the participatory management of the Technological Incubators of Popular Cooperatives in Brazilian public universities, allied with the precepts of Responsible Research and Innovation (RRI). The study had as a paradigmatic example the education, research and extension initiatives offered by the Integrated Multidisciplinary Nucleus of Studies, Training and Intervention in Solidarity Economy (NuMI-EcoSol) of the Federal University of São Carlos (UFSCar), extending the analysis to Technological Incubators of Popular Cooperatives of other three public universities in the State of São Paulo: University of São Paulo (USP), State University of Campinas (Unicamp) and São Paulo State University (Unesp). The study mainly questioned: (i) if the public engagement of science is inserted – and how this insertion occurs – in the participatory management process of the incubators; (ii) whether the RRI precepts are present in the official documents and in the institutional communication vehicles of these incubators; and (iii) in what ways the public engagement of science can act as a facilitator in action policies within the scope of education, research and extension activities in incubators, optimizing participatory management among the agents involved. This qualitative exploratory research used, as methodologies, (i) bibliographic analysis about Public Communication of Science, RRI, solidary economy and Technological Incubators of Popular Cooperatives; (ii) documentary analysis, with analysis of online files; (iii) application of a questionnaire with agents who work at incubators; and (iv) content analysis of the interviews granted by researchers from incubators and specific indicators and criteria for institutional online tools (website and social networks), to reflect if the precept of public engagement by RRI agrees with the dissemination of the incubators' actions and in what ways this precept can act as a facilitator in promoting public participation. The development of the research was guided by the hypothesis that some aspects of the incubators of Brazilian public universities – the fact that they are self-managed, make collective decisions and aim to involve the target audiences in decision-making, which include several agents of the society – favor the promotion of public engagement of science, within the scope of the RRI, in initiatives that involve the inseparability between education, research and extension. Based on the research, it was observed that incubators have participatory movements in their daily actions, whether online or offline, but this is still a challenge. The main obstacles to strengthening this public engagement are: (i) lack of government support and, consequently, lack of funds and human resources; (ii) difficulty in accessing the external public and consequent engagement; and (iii) difficulty in encouraging the participation of the external public in forums and events with a certain frequency. The research suggested ways for these incubators to advance the awareness – and active participation - of the target audiences and possible actions that can be put into practice, with the proposition of recommendations that assist in promoting public engagement and in the construction of a bidirectional communication, participatory and aligned with the missions of the incubators’ activities.